ANALYSIS OF THE EFFECTIVENESS OF USING POWER IN LEADERSHIP - Solichin, Endang (Dinasti International Journal of Management Science, 2019)
Institutions that can survive and thrive are institutions that have leaders who have a vision of very sharp changes and are able to transform organizational capabilities to build competitiveness. The success of a leader is largely determined by the ability to know and use the right kind of power in accordance with the demands of the situation. The purpose of this study is to analyze the effectiveness of the use of different kinds of power in leadership. These types of powers are expertise, reference power, reward power, legal authority and coercive power. This research was conducted at STKIP YPM in Merangin district, Jambi Province, Indonesia. The sample in this study were 30 lecturers from a population of 66 lecturers. Analysis of the data used to answer the objectives of this study is the Spearman Rank-Order Correlation with a significant level of 5%. This research results that the use of expertise power, reference power, legal power and coercive power does not have a significant correlation with the attitude of commitment of the lecturers while the use of reward power has a significant negative correlation with the attitude of commitment of the lecturer.